Analysis of the Effectiveness of Blended-Based Classroom Management During the Covid-19 Pandemic - Lathifah, Zahra Khusnul; Adri, Helmia Tasti; Utami, Irma Inesia Sri; Sya, Mega Febriani; Uslan, Uslan (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The policy of adapting new habits during the COVID-19 pandemic in yellow and green zone schools became the basis for blended learning practices at SDIT AlFatih Cigombong, which became a pilot school in the Bogor Regency area. This study aims to analyze the effectiveness of blended-based classroom management at SDIT Al-Fatih. This study uses a qualitative approach with a qualitative descriptive method. The data were collected through interview, observation, documentation, and literature study. The data analysis method used descriptive analysis techniques. Research findings show that blended-based classroom management at SDIT Al-Fatih during the COVID19 pandemic was declared quite effective. It indicated from some aspects: teacherâ€™s ability to manage learning, utilize learning media optimally, positive response of students to learning activities, learning objectives can be achieved, quantity of student assignments, giving fair rewards and grades to students, periodic assessments, classical minimum completeness criteria (KKM) achievement, actively involving students, attracting studentsâ€™ interest and attention, active communication between teachers and parents regarding information related to student and school learning, having facilities and infrastructure to support the teaching and learning process. Furthermore, implementing blended-based learning considered effective in maximizing learning activities during the Covid-19 pandemic.Â